Crossroads at the linguistic market - Antiqua-Parlee, M.J. (Linguistica Atlantica, 2017)
Local identity practices are not as straightforward as originally predicted (Labov 1972a, 1963). I buildon previous work on local identity practices in coastal rural communities (e.g. Josey 2004, Labov1972a, Wolfram 1997) in an investigation of feature maintenance and identity practices on MountDesert Island, a tourist-dependent community in New England. Based on sociolinguistic interviewswith 12 native speakers of the MDI community, I find that the use of a local feature, the dropping ofpost-vocalic R (e.g. “car”, pronounced variably as [ka:], is moribund in the community. Ther-less variant is still in use by older speakers, and among these speakers a gender pattern and a pattern with respect to a speaker's source of capital emerge (Bourdieu 1991, 1972, 1986).